A etiologia multifatorial da recessão periodontal - Yared, Karen Ferreira Gazel; Zenobio, Elton Gonçalves [UNESP]; Pacheco, Wellington (Dental Press Editora, 2006)
The literature shows that besides dental plaque, some external and anatomic local factors are still related to gingival recession etiology. This study reviewed the literature about those factors, which knownledge is of great benefit to the orthodontist, contributing during diagnostic, planning and orthodontic treatment.

A literatura apresenta vários fatores relacionados na etiologia da recessão periodontal, além do processo inflamatório induzido pelo biofilme bacteriano, os quais incluem fatores externos e anatômicos locais. Por meio deste estudo, revistou-se a literatura sobre tais fatores, cujo conhecimento é de grande importância para o ortodontista, contribuindo durante o diagnóstico, planejamento e tratamento ortodôntico propriamente dito.
The etiologic factors of periodontal recession
Keywords: Gingival recession; Etiology; Mucogingival alterations; Recessão gengival; Etiologia; Alterações mucogengivais